Litterfall and nutrients return in Nothofagus antarctica forests growing in a site quality gradient with different management uses in Southern Patagonia - Bahamonde, Nora; Peri, Pablo Luis; Martínez Pastur, Guillermo José; Monelos, L. (European Journal of Forest Research)
We evaluated the annual litterfall and nutrients return in primary forests of Nothofagus antarctica growing at three different site classes (SC) (III, IV and V) and compared two of these forests with adjacent stands under silvopastoral use (thinned 40 years ago), in Patagonia, Argentina. Traps were installed in each stand and sampled monthly during the litterfall over 10 years. Sample from the five stands was ground for further analyses of nutrients (N, P, K, Ca, Mg and S). The litterfall varied significantly between SC, but not between years, from 1,306 to 1,972 kg ha−1 in the best site. The nutrients return from litterfall did not change neither between site classes and years in most nutrients. Comparing primary forests with silvopastoral stands, in SCIV, significant differences among uses occurred for litterfall production and nutrients return, being higher in primary forest. While, in SCV, the litterfall and nutrients return practically did not change among uses. The results showed the incidence of site quality and forest use on the litterfall and nutrients return in N. antarctica forests. Fil: Bahamonde, Nora. Instituto Nacional de Tecnología Agropecuaria; Argentina. Universidad Nacional de la Patagonia Austral; Argentina Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria; Argentina. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Monelos, L. Universidad Nacional de la Patagonia Austral; Argentina